Die Ou Testament en/in die kerk van Jesus Christus? - Snyman, S. D. (Verbum et ecclesia, 2007)
The question raised in this contribution is suggested in the title: Should the place of the Old Testament be regarded as outside of, over against and thus not really part of the church or should the Old Testament be regarded as in the church as part of the canon of scriptures together with the New Testament. A historical overview is given to illustrate a movement in the interpretation of the Old Testament that started initially as a christological interpretation but developed in a more theological appreciation of the Old Testament. It is further indicated that the emphasis in both the exegesis and theology of the Old Testament is on the Old Testament's own theological integrity. Therefore there is no pressing need for a christological interpretation of the Old Testament as if that would be the one and only valid way of reading the Old Testament.